Role of laboratory examinations in the diagnosis of vasomotor rhinitis: A Review of Literature - Arfiana, Nur Wisma; Jayati, Nurul Sari; Zufar, M Irvan; Putra, Kresna Aditya Nugraha; Hasmy, Alya Fauzizah; Puspitasari, Metana (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2025)
Introduction: Vasomotor rhinitis (VMR) is a subtype of non-allergic rhinitis characterized by chronic nasal symptoms such as congestion, rhinorrhea, and sneezing without allergic or infectious causes. The absence of specific biomarkers makes VMR difficult to distinguish from allergic rhinitis, resulting in diagnostic challenges and potentially inappropriate therapy. This review aims to assess the contribution of laboratory examinations in the differential diagnosis of VMR. Methods: A comprehensive literature search was performed using PubMed and Google Scholar databases for articles published between January 2021 and September 2025. Keywords included “non-allergic rhinitis,” “laboratory,” “IgE,” “eosinophil,” “nasal cytology,” “FeNO,” and “biomarker.” Out of 8,350 identified publications, 407 titles were relevant, and 57 full-text articles were reviewed. After applying inclusion and exclusion criteria, nine studies were selected for detailed analysis. Results: No single laboratory test can confirm the diagnosis of VMR. Total and specific IgE levels, as well as peripheral eosinophil counts, mainly serve to exclude allergic rhinitis. Nasal cytology plays a crucial role in identifying subtypes of non-allergic rhinitis, including NARES and NARNE. Measurements of nasal nitric oxide (nNO/FeNO) and newer biomarkers, including diamine oxidase (DAO), show potential as supportive indicators, though findings remain inconsistent. Conclusion: Laboratory examinations contribute primarily as adjunctive tools in differentiating VMR from allergic rhinitis. A multimodal diagnostic approach that integrates serological, cytological, and biomarker evaluations with clinical findings offers the most reliable strategy for improving diagnostic accuracy and guiding appropriate therapy.